Analysis Of The Added Value Of Goat Manure As Organic Fertilizer In Carangwulung Village, Wonosalam District - Rizkiyah, Salsabila Putri Ainur; Avivah, Elmira Dhiva; Armana, Andru; Rahman, Toriq Aulia; Rozci, Fatchur (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
The high population of goats in Carangwulung Village causes high amounts of animal waste to be produced on the goat farm, of course, this must be managed well so that it does not hurt the environment. The chairman of LMDH